The use of holiday biography in generation-based ‘tourism space’ research - Kowalczyk-Anioł, Joanna (Turyzm/Tourism, 2013)
The article presents the concept of generation-based ‘tourism space’ research using the holiday biography method. The author refers to her earlier research conducted among three generations of Łodź families. She discusses the biography method used in the research and approaches it from a geo-biographical point of view, showing possible ways of recording the phenomenon (the particular character of the source material collected) and the various options available at later stages of research – interpretation (choosing the analysis, measurement and presentation methods) – and generalization.